2005
DOI: 10.1007/11426639_4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Complexity Assumptions for Statistically-Hiding Commitment

Abstract: Determining the minimal assumptions needed to construct various cryptographic building blocks has been a focal point of research in theoretical cryptography. Here, we revisit the following question: what are the minimal assumptions needed to construct statistically-hiding commitment schemes? Previously, it was known how to construct such schemes based on one-way permutations. We improve upon this by constructing statistically-hiding commitment schemes based on approximable-preimage-size one-way functions. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…2 Conditional multiple-mutual information is also called conditional kinformation [20]- [22]. 3 The definition of a balanced source here is different from that by Haitner et al [25,Sec. 3].…”
Section: A Balanced Sourcesmentioning
confidence: 99%
“…2 Conditional multiple-mutual information is also called conditional kinformation [20]- [22]. 3 The definition of a balanced source here is different from that by Haitner et al [25,Sec. 3].…”
Section: A Balanced Sourcesmentioning
confidence: 99%
“…One-round statistically-hiding commitments can be based on any collision-resistant hash function [19,48]. Tworound statistically-hiding commitments can be based on any claw-free collection with an efficiently recognizable index set [38,36,34] (statistically-hiding commitments can also be based on general assumptions, in particular any OWF, with non-constant rounds [61,47,46]).…”
Section: Prover Auxiliary Inputmentioning
confidence: 99%
“…A construction of statistically-hiding scheme (NOVY scheme) from one-way permutation was given by Naor, Ostrovsky, Venkatesan and Yung [24]. After that, the assumption of the existence of one-way permutation was relaxed to that of approximable-preimage-size one-way function [12]. Finally, Haitner and Reingold [15] showed that a statistically-hiding scheme (HNORV scheme [13]) can be based on any one-way function.…”
Section: Introductionmentioning
confidence: 99%